A negative electrode material and its preparation method and application

By using a low-eutectic solvent to eutectic silk to coat natural graphite, the problems of poor electrolyte compatibility and fast charging capacity of natural graphite negative electrode materials are solved, and better rate performance and cycles are achieved stability.

CN116525803BActive Publication Date: 2025-02-21SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310710763.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2025-02-21
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

The existing natural graphite negative electrode materials have problems such as poor electrolyte compatibility and poor fast charging capabilities, and cannot meet the needs of high energy density, long cycle life, and large current charging and discharging capabilities.

Method used

Silk nanoprotein fibers were prepared as coating agent by eutectic solvent eutectic silk, and negative electrode materials with improved magnification difference and cycle stability were prepared by mixing with natural graphite and sintering.

Benefits of technology

It significantly improves the rate performance and cycle stability of the battery, and is suitable as the negative electrode material of the power battery. Compared with the traditional method, the cycle performance is improved by nearly 1.5%, and the capacity is increased by 28.5mAh/g after 50 cycles at 5C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116525803B_ABST
    Figure CN116525803B_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing choline chloride and ethylene glycol, performing heat treatment to obtain an ethylene glycol / choline chloride low eutectic solvent, mixing pretreated silk with the ethylene glycol / choline chloride low eutectic solvent for reaction, adding deionized water to terminate the reaction to obtain a slurry-like substance; (2) mixing graphite with the slurry-like substance obtained in step (1), and obtaining a precursor through post-treatment; (3) sintering the precursor obtained in step (2) to obtain the negative electrode material. The present invention adopts the prepared silk fibroin nano-protein fibers as a coating agent, which can not only effectively improve the rate difference problem of natural graphite negative electrode materials, but also improve the cycle stability of the materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a negative electrode material and a preparation method and application thereof. Background Art

[0002] The new energy sector is facing historic opportunities and challenges, among which lithium-ion secondary batteries, which are economical, environmentally friendly and reusable, have become the focus of current research. The negative electrode material plays a vital role in the entire battery system.

[0003] At present, the theoretical specific capacity (372mAh / g) and high current charge and discharge capacity of commercial graphite negative electrode materials can no longer meet the current development needs. Therefore, the development of other carbon negative electrode materials with high energy density, long cycle life, and high current charge and discharge capacity has become the key to building high specific energy lithium batteries. Natural graphite has attracted much attention due to its high capacity, low cost, and abundant reserves, but its main disadvantage is its poor fast charging ability. Therefore, the liquid phase coating method that is easy to evenly coat can be used to improve the fast charging performance of natural graphite.

[0004] Natural graphite has poor electrolyte compatibility and poor fast charging capability as negative electrode material for lithium-ion batteries, and cannot be used as negative electrode material without coating. Therefore, a uniformly coated liquid phase coating method can be used to improve the fast charging performance of natural graphite.

[0005] CN112186165A discloses a lithium ion battery negative electrode material with high specific capacity, good cycle stability and long service life. It uses a silkworm cocoon degumming process, an in-situ growth process and a high-temperature calcination process to obtain a fiber material loaded with Ni nanoparticle protein. Silk becomes carbon fiber after carbonization, but the structural damage of the amorphous carbon fiber when reacting with lithium ions causes capacity decay, so nickel acetate is added. Nickel metal can promote the stability of the solid electrolyte interface and enhance the stability of the electrochemical cycle. Ni nanoparticle protein fiber material is expected to be used as a cheap energy storage negative electrode material.

[0006] CN113422057A discloses a phenolic resin coated graphite negative electrode material and a preparation method thereof. The graphite negative electrode material comprises the following components in weight fractions: 3-5wt% of phenolic resin, 1-2wt% of dispersant, 0.5-1wt% of dispersing aid, and 93-95.5wt% of graphite; the dispersant is selected from any one of dodecyl dimethyl betaine, tetradecyl dimethyl betaine, octadecyl dimethyl betaine, and octadecyl dihydroxyethyl betaine, or a mixture of several of them; the dispersing aid is selected from any one of glucose, lactic acid, and malic acid.

[0007] In the above-mentioned scheme for preparing coated graphite materials, the preparation process needs to be optimized and improved, and the rate performance needs to be further improved. Summary of the invention

[0008] The purpose of the present invention is to provide a negative electrode material and a preparation method and application thereof. The present invention uses the prepared silk fibroin nano-protein fibers as a coating agent, which can not only effectively improve the rate difference problem of natural graphite negative electrode materials, but also improve the cycle stability of the material.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a negative electrode material, the preparation method comprising the following steps:

[0011] (1) mixing choline chloride and ethylene glycol, performing heat treatment to obtain an ethylene glycol / choline chloride low eutectic solvent, mixing the pretreated silk with the ethylene glycol / choline chloride low eutectic solvent to react, and adding deionized water to terminate the reaction to obtain a slurry-like substance;

[0012] (2) mixing graphite with the slurry obtained in step (1), and obtaining a precursor through post-treatment;

[0013] (3) Sintering the precursor obtained in step (2) to obtain the negative electrode material.

[0014] In the preparation method of the present invention, silk materials are widely available, the material preparation method is mild and controllable, the prepared natural graphite negative electrode material coated with silk fibroin nano-protein fibers has good electrochemical performance, can significantly improve the rate performance of the battery, and has broad research value in practical applications.

[0015] Preferably, the mass ratio of choline chloride to ethylene glycol in step (1) is (1.5-3.0):2, for example: 1.5:2, 1.8:2, 2:2, 2.2:2 or 3:2, etc.

[0016] Preferably, the temperature of the heat treatment is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C or 100°C.

[0017] Preferably, the pretreatment in step (1) comprises washing the silk with deionized water 2 to 4 times and then drying it.

[0018] Preferably, the drying temperature is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C.

[0019] Preferably, the mass ratio of the silk to the ethylene glycol / choline chloride eutectic solvent is (1-1.2):1, for example: 1:1, 1.05:1, 1.1:1, 1.15:1 or 1.2:1, etc.

[0020] Preferably, stirring is performed during the reaction in step (1).

[0021] Preferably, the reaction time is 3 to 5 h, for example, 3 h, 3.5 h, 4 h, 4.5 h or 5 h.

[0022] Preferably, the mass of the deionized water is the same as that of the ethylene glycol / choline chloride deep eutectic solvent.

[0023] Preferably, the graphite in step (2) comprises natural graphite.

[0024] Preferably, the median particle size D50 of the graphite is 7 to 15 μm, for example, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm or 15 μm.

[0025] Preferably, the mass ratio of the graphite to the slurry-like substance is (5-30):100, for example: 5:100, 10:100, 15:100, 20:100 or 30:100, etc.

[0026] Preferably, the post-treatment in step (2) includes liquid nitrogen spray pre-freezing treatment and freeze-drying treatment.

[0027] Preferably, the temperature of the sintering treatment in step (3) is 800-1200°C, for example, 800°C, 900°C, 1000°C, 1100°C or 1200°C.

[0028] Preferably, the sintering treatment time is 2 to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0029] Preferably, the atmosphere of the sintering process includes nitrogen.

[0030] In a second aspect, the present invention provides a negative electrode material, which is prepared by the method described in the first aspect.

[0031] Compared with traditional graphite negative electrode materials, the negative electrode material of the present invention has better cycle stability and better high-rate charge and discharge performance, and is suitable as a negative electrode material for power batteries.

[0032] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the negative electrode material as described in the second aspect.

[0033] In a fourth aspect, the present invention provides a battery, comprising the negative electrode plate as described in the third aspect.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The coating material added to the negative electrode material of the present invention is a silk fibroin nanofiber obtained by eutectic silk with a low eutectic solvent. The silk fibroin nanofiber as a coating agent can not only effectively improve the rate difference problem of natural graphite negative electrode materials, but also improve the cycle stability of the material.

[0036] (2) The present invention uses cheap silk as the coating material, and the ethylene glycol / choline chloride eutectic solvent is low in cost and clean and environmentally friendly. The preparation process is novel, green, and has no harmful gas output. The silk fibroin nanofibers prepared based on the ethylene glycol / choline chloride eutectic solvent can improve the conductivity of the material and is conducive to the formation of a stable SEI film.

[0037] (3) The present invention uses low eutectic solvent eutectic silk as a coating agent, and the cycle performance of the material coated with silk alone is improved by nearly 1.5% compared to that of the material coated with silk alone, and the capacity is increased by 28.5 mAh / g after 50 cycles at a rate of 5C; the cycle performance of the conventional biomass material cotton is improved by nearly 5.0%, and the capacity is increased by 43.8 mAh / g after 50 cycles at a rate of 5C. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a comparison chart of the cycle performance of the negative electrode materials prepared in Example 1 of the present invention and Comparative Example 1.

[0039] Figure 2 This is a rate performance diagram of the negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0041] The ethylene glycol / choline chloride deep eutectic solvent used in the examples and comparative examples of the present invention was prepared by the following method:

[0042] Choline chloride and ethylene glycol were mixed in a molar ratio of 2:1, and the mixture was heated to 90°C and stirred until a completely homogeneous liquid was formed.

[0043] Example 1

[0044] This embodiment provides a negative electrode material, and the preparation method of the negative electrode material is as follows:

[0045] (1) Weigh 10 g of silk, wash it three times with deionized water, put it in a 60° C. oven to dry, and then immerse it in 10 g of ethylene glycol / choline chloride eutectic solvent. Stir it with a magnetic stirrer for 4 h, then add deionized water (with the same mass as the eutectic solvent) to terminate the reaction, and obtain a slurry-like substance;

[0046] (2) mixing a finished natural graphite powder having a median particle size D50 of 10 μm with a slurry-like substance at a mass ratio of 20%, and then pre-freezing the mixture by liquid nitrogen spraying, and then quickly transferring the pre-frozen precursor material to a freeze dryer for vacuum sublimation drying to obtain a precursor material;

[0047] (3) placing the vacuum sublimation dried precursor in a tube furnace, annealing it at 900° C. for 3 h at a heating rate of 5° C. / min in a nitrogen atmosphere, and naturally cooling it to room temperature to obtain the negative electrode material.

[0048] Example 2

[0049] This embodiment provides a negative electrode material, and the preparation method of the negative electrode material is as follows:

[0050] (1) Weigh 10 g of silk, wash it three times with deionized water, put it in a 60° C. oven to dry, and then immerse it in 10 g of ethylene glycol / choline chloride eutectic solvent. Stir it with a magnetic stirrer for 4 h, then add deionized water (with the same mass as the eutectic solvent) to terminate the reaction, and obtain a slurry-like substance;

[0051] (2) mixing a finished natural graphite powder having a median particle size D50 of 10 μm with a slurry-like substance at a mass ratio of 15%, and then pre-freezing the mixture by spraying liquid nitrogen, and then quickly transferring the pre-frozen precursor material to a freeze dryer for vacuum sublimation drying to obtain a precursor material;

[0052] (3) placing the vacuum sublimation dried precursor in a tube furnace, annealing it at 1000° C. for 2 h at a heating rate of 5° C. / min in a nitrogen atmosphere, and naturally cooling it to room temperature to obtain the negative electrode material.

[0053] Example 3

[0054] This embodiment provides a negative electrode material, and the preparation method of the negative electrode material is as follows:

[0055] (1) Weigh 7 g of silk, wash it three times with deionized water, put it in a 60° C. oven to dry, and then immerse it in 10 g of ethylene glycol / choline chloride eutectic solvent. Stir it with a magnetic stirrer for 4 h, then add deionized water (with the same mass as the eutectic solvent) to terminate the reaction, and obtain a slurry-like substance;

[0056] (2) mixing a finished natural graphite powder having a median particle size D50 of 10 μm with a slurry-like substance at a mass ratio of 25%, and then pre-freezing the mixture by spraying liquid nitrogen, and then quickly transferring the pre-frozen precursor material to a freeze dryer for vacuum sublimation drying to obtain a precursor material;

[0057] (3) placing the vacuum sublimation dried precursor in a tube furnace, annealing it at 1100° C. for 2 h at a heating rate of 5° C. / min in a nitrogen atmosphere, and naturally cooling it to room temperature to obtain the negative electrode material.

[0058] Example 4

[0059] This embodiment provides a negative electrode material, and the preparation method of the negative electrode material is as follows:

[0060] (1) Weigh 10 g of silk, wash it three times with deionized water, put it in a 60° C. oven to dry, and then immerse it in 10 g of ethylene glycol / choline chloride eutectic solvent. Stir it with a magnetic stirrer for 4 h, then add deionized water (with the same mass as the eutectic solvent) to terminate the reaction, and obtain a slurry-like substance;

[0061] (2) mixing a finished natural graphite powder having a median particle size D50 of 10 μm with a slurry-like substance at a mass ratio of 30%, and then pre-freezing the mixture by spraying liquid nitrogen, and then quickly transferring the pre-frozen precursor material to a freeze dryer for vacuum sublimation drying to obtain a precursor material;

[0062] (3) The precursor after vacuum sublimation drying is placed in a tube furnace, annealed at 800° C. for 4 h in a nitrogen atmosphere at a heating rate of 5° C. / min, and naturally cooled to room temperature to obtain the negative electrode material.

[0063] Example 5

[0064] The only difference between this embodiment and embodiment 1 is that the mass ratio of silk to ethylene glycol / choline chloride eutectic solvent is 5:10, and other conditions and parameters are exactly the same as those in embodiment 1.

[0065] Example 6

[0066] The only difference between this embodiment and embodiment 1 is that the mass ratio of silk to ethylene glycol / choline chloride eutectic solvent is 15:10, and other conditions and parameters are exactly the same as those in embodiment 1.

[0067] Example 7

[0068] The only difference between this embodiment and embodiment 1 is that the liquid nitrogen spray pre-freezing process is replaced by a vacuum drying process, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0069] Comparative Example 1

[0070] This comparative example provides a negative electrode material, and the preparation method of the negative electrode material is as follows:

[0071] Weigh 10g of silk, place it in a NaHCO3 aqueous solution, boil and wash it, mix the finished natural graphite powder and the silk solution in a mass ratio of 20% to obtain a precursor material, then perform liquid nitrogen spray pre-freezing treatment, and then quickly transfer the pre-frozen precursor material to a freeze dryer for vacuum sublimation drying. Place the vacuum sublimation dried precursor in a tubular furnace, anneal at 900°C in a nitrogen atmosphere at a heating rate of 5°C / min for 2 hours, and naturally cool to room temperature to obtain the negative electrode material.

[0072] Comparative Example 2

[0073] In this comparative example, conventional biomass material cotton is used for coating.

[0074] Performance Testing:

[0075] 1) Using NMP (N-methylpyrrolidone) as a solvent to prepare a 5% PVDF (polyvinylidene fluoride) solution, the negative electrode material prepared in the embodiment and the comparative example, acetylene black, and the 5% PVDF solution were mixed in a mass ratio of 94:2:4, and stirred with a magnetic stirrer for 12 hours to make the mixture uniform, thereby preparing an electrode slurry;

[0076] 2) The prepared electrode slurry was evenly coated on a clean copper foil, vacuum dried at 110° C., and the copper foil was cut into circular electrode sheets with a diameter of 16 mm using a cutting machine;

[0077] 3) Wrap the treated copper foil electrode sheet up and down, place it in a flat and clean mold, press it under a pressure of 12Mpa, and then assemble the button half-cell in a glove box, using the active material as natural graphite coated with silk nano-protein fibers as the positive electrode and the lithium sheet as the negative electrode. Use the LAND battery test system to test the charge and discharge performance of the three batteries at a rate of 1C. The test results are shown in Table 1:

[0078] Table 1

[0079]

[0080]

[0081] As can be seen from Table 1, from Examples 1-4 and Comparative Examples 1-2, the present invention uses low eutectic solvent eutectic silk as a coating agent, compared with the pure silk as a coating agent, the cycle performance of the material is improved by nearly 1.5%, and the capacity is increased by 28.5 mAh / g after 50 cycles at a rate of 5C; compared with the conventional biomass material cotton, the cycle performance is improved by nearly 5.0%, and the capacity is increased by 43.8 mAh / g after 50 cycles at a rate of 5C.

[0082] By comparing Example 1 with Examples 5-6, it can be seen that the mass ratio of silk and ethylene glycol / choline chloride low eutectic solvent in the preparation process of the negative electrode material of the present invention affects its performance. The mass ratio of silk and ethylene glycol / choline chloride low eutectic solvent is controlled at (1-1.2): 1, and the performance of the obtained negative electrode material is better. If the amount of silk is too large, the coating amount is too much, the cycle performance of the material deteriorates, and the kinetic performance is slightly improved. If the amount of silk is too small, the kinetic performance of the material is insufficient, and the cycle performance is roughly the same.

[0083] By comparing Example 1 and Example 7, it can be seen that the method of pre-freezing and then freeze-drying adopted in the present invention can make the silk and ethylene glycol / choline chloride low eutectic solvent and the negative electrode material natural graphite evenly coated, which is beneficial to maintain the excellent amorphous carbon structure formed on the coated surface, thereby ensuring the dynamic properties of the material.

[0084] The cycle performance comparison of the negative electrode materials obtained in Example 1 and Comparative Example 1 is shown in the figure Figure 1 As shown, the rate performance diagram of the negative electrode material prepared in Example 1 is as follows Figure 2 As shown, by comparing Example 1 with Comparative Example 1, it can be obtained that the natural graphite negative electrode material coated with the silk fibroin nano-protein fibers obtained in the present invention has better capacity retention performance.

[0085] By comparing Example 1 and Comparative Example 2, it can be seen that compared with commonly used biomass coating materials, the coating material added to the negative electrode material of the present invention is silk fibroin nanoprotein fibers obtained by eutectic silk with a low eutectic solvent. The silk fibroin nanoprotein fibers as a coating agent can not only effectively improve the rate difference problem of natural graphite negative electrode materials, but also improve the cycle stability of the material.

[0086] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a negative electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing choline chloride and ethylene glycol, and subjecting them to heat treatment to obtain an ethylene glycol / choline chloride low eutectic solvent, mixing the pretreated silk with the ethylene glycol / choline chloride low eutectic solvent to react, and adding deionized water to terminate the reaction to obtain a slurry-like substance; The mass ratio of the silk and the ethylene glycol / choline chloride eutectic solvent is (1-1.2):1; The pretreatment includes washing the silk with deionized water 2 to 4 times and then drying; (2) mixing graphite with the slurry obtained in step (1), and obtaining a precursor through post-treatment; The post-treatment includes liquid nitrogen spray pre-freezing treatment and freeze-drying treatment; (3) Sintering the precursor obtained in step (2) to obtain the negative electrode material.

2. The preparation method according to claim 1, characterized in that The mass ratio of choline chloride to ethylene glycol in step (1) is (1.5-3.0):

2.

3. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment is 80-100°C.

4. The preparation method according to claim 1, characterized in that: The drying temperature is 50-70°C.

5. The preparation method according to claim 1, characterized in that: Stirring is performed during the reaction in step (1).

6. The preparation method according to claim 1, characterized in that: The reaction time is 3 to 5 hours.

7. The preparation method according to claim 1, characterized in that: The mass of the deionized water added to terminate the reaction is the same as the mass of the ethylene glycol / choline chloride deep eutectic solvent.

8. The preparation method according to claim 1, characterized in that: The graphite in step (2) includes natural graphite.

9. The preparation method according to claim 1, characterized in that: The median particle size D50 of the graphite is 7-15 μm.

10. The preparation method according to claim 1, characterized in that: The mass ratio of the graphite to the slurry-like substance is (5-30):

100.

11. The preparation method according to claim 1, characterized in that: The sintering temperature in step (3) is 800-1200°C.

12. The preparation method according to claim 1, characterized in that: The sintering time is 2 to 4 hours.

13. The preparation method according to claim 1, characterized in that: The atmosphere of the sintering process includes nitrogen.

14. A negative electrode material, characterized in that: The negative electrode material is prepared by the method according to any one of claims 1 to 13.

15. A negative electrode plate, characterized in that: The negative electrode sheet comprises the negative electrode material as claimed in claim 14.

16. A battery, characterized in that: The battery comprises the negative electrode sheet as claimed in claim 15 .

Citation Information

Patent Citations

  • Ni nanoparticle-loaded protein fiber as well as preparation method and application of protein fiber

    CN112186165A

  • Phenolic resin coated graphite negative electrode material and preparation method thereof

    CN113422057A

  • Method for directly extracting fibroin nanofiber and recovering hydrolyzed silk protein and extracting solution from waste silkworm cocoons

    CN114163684A

  • Nitrogen-rich amorphous carbon liquid phase coated graphite negative electrode material and preparation method thereof

    CN115241444A

  • Ultra-thin hollow carbon nanospheres for sodium ion storing and manufacturing method thereof

    KR1020160124964A